2021
DOI: 10.1001/jamaneurol.2021.3188
|View full text |Cite
|
Sign up to set email alerts
|

Use and Safety of Immunotherapeutic Management of N-Methyl-d-Aspartate Receptor Antibody Encephalitis

Abstract: Key Points Question What are the most effective treatments for N -methyl- d -aspartate receptor (NMDAR) antibody encephalitis? Findings In this meta-analysis of individual patient data including 1550 cases, treatment factors at first event that were significantly associated with good functional outcome 12 months from disease onset included first-line treatment with therapeutic apheresis alone, corticoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
129
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(171 citation statements)
references
References 69 publications
7
129
2
Order By: Relevance
“…The majority of patients initially present subacute psychiatric symptoms such as mania, social withdrawal, and psychosis. Subsequently, this initial clinical picture is rapidly followed by neurological abnormalities including short-term memory impairment, seizures, movement disorders, central hypoventilation, and even altered level of consciousness leading to intensive care unit (ICU) in up to 50% of adult patients [ 14 ]. Nonetheless, movement disorders and partial seizures are more frequently the first symptom in children [ 15 , 16 ], while male adults often have isolated focal seizures preceding the full clinical picture [ 17 ].…”
Section: An Overview Of Anti-nmdar Encephalitismentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of patients initially present subacute psychiatric symptoms such as mania, social withdrawal, and psychosis. Subsequently, this initial clinical picture is rapidly followed by neurological abnormalities including short-term memory impairment, seizures, movement disorders, central hypoventilation, and even altered level of consciousness leading to intensive care unit (ICU) in up to 50% of adult patients [ 14 ]. Nonetheless, movement disorders and partial seizures are more frequently the first symptom in children [ 15 , 16 ], while male adults often have isolated focal seizures preceding the full clinical picture [ 17 ].…”
Section: An Overview Of Anti-nmdar Encephalitismentioning
confidence: 99%
“…Supporting this hypothesis, Chefdeville et al found that ovarian teratomas associated with anti-NMDAR encephalitis contain nervous glial tissue, and among them, 82% express the GluN1 subunit of the NMDAR [ 20 ]. However, a recent meta-analysis showed that paraneoplastic cases account for only 25% of cases [ 14 ], suggesting that other unknown pathogenic mechanisms may lead to the immune tolerance breakdown in anti-NMDAR encephalitis. Likewise, a few viral infections have been reported as triggers of anti-NMDAR encephalitis, especially herpes simplex 1 virus (HSV1) encephalitis [ 13 , 21 , 22 ].…”
Section: An Overview Of Anti-nmdar Encephalitismentioning
confidence: 99%
See 3 more Smart Citations